2017
DOI: 10.5114/ada.2017.72464
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function and thyroid autoantibodies in patients with chronic spontaneous urticaria

Abstract: IntroductionChronic urticaria (CU) is a skin disease caused by autoantibodies against high affinity immunoglobulin E (IgE) receptor and against IgE. It is characterized by hives, erythematous wheals and redness present minimum twice a week for at least 6 weeks. It is observed that there is a strong association between CU and autoimmune diseases, such as autoimmune thyroiditis (AT).AimTo verify the frequency of AT in patients suffering from chronic spontaneous urticaria (CSU) and to confirm the coexistence of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
5
0
2
Order By: Relevance
“…Moreover, some studies reported Tg receptor expression in non-thyroid tissue such as skin and human brain thus suggesting a role of Tg in these tissues (Naicker and Naidoo, 2018) which then implies that TgAb antibodies may disrupt that role. There is known connection of thyroid autoimmunity with skin disorders like chronic urticaria (Czarnecka-Operacz and Sadowska-Przytocka et al, 2017), vitiligo (Baldini and Odorisio et al, 2017) and increased skin autoreactivity (Turkoglu and Zindanci et al, 2012). One case report already documented an association of TgAb with facial edema in euthyroid individual (Miralles and Soriano et al, 2002) thus providing more evidence for our finding.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, some studies reported Tg receptor expression in non-thyroid tissue such as skin and human brain thus suggesting a role of Tg in these tissues (Naicker and Naidoo, 2018) which then implies that TgAb antibodies may disrupt that role. There is known connection of thyroid autoimmunity with skin disorders like chronic urticaria (Czarnecka-Operacz and Sadowska-Przytocka et al, 2017), vitiligo (Baldini and Odorisio et al, 2017) and increased skin autoreactivity (Turkoglu and Zindanci et al, 2012). One case report already documented an association of TgAb with facial edema in euthyroid individual (Miralles and Soriano et al, 2002) thus providing more evidence for our finding.…”
Section: Discussionsupporting
confidence: 69%
“…34 Several studies suggest that adequate therapy with antithyroid drugs or levothyroxine in early stages may help to achieve remission of CSU. 44 Kim et al reported that 2 out of 10 patients with CSU and HT, showed improvement in urticaria symptoms when levothyroxine was administered. 35 Magen et reported that patients with CSU and hypothyroidism, showed a decrease of the urticaria activity score (UAS) when levothyroxine was added to the treatment; nevertheless, in euthyroid patients, there was no significant difference after 3-6 months of levothyroxine treatment.…”
Section: Treatment Of Urticaria and Autoimmune Thyroid Diseasementioning
confidence: 99%
“…Increased levels of D-dimers are associated with increased platinum processing of fibrin. What is also significant is that D-dimers are also responsible for the release of histamine from mast cells [ 11 , 12 ]. It seems that markers of haemostasis can be useful in monitoring the activity of the disease process in the course of CSU and the effects of its treatment.…”
Section: Discussionmentioning
confidence: 99%